Análise de percepções acerca do processo de ensino e aprendizagem de cirurgia em pequenos animais no curso de Medicina Veterinária - Honji, Rubens Machado (2019)
Introduction: Brazil is the country with the most number of Veterinary Medicine colleges in the world and in the National Curricular Guidelines for Undergraduate Courses, wich the egress’ profile includes theoretical and practical content related to veterinary surgery. Aim: Analyze the perceptions about the teaching and learning in small animals’ surgery, in Veterinary Medicine Education Programs, from the perspective of teachers, students and professionals. Method: The sample included four teachers, five students and five newly veterinary professionals from different educational institutions. The open interviews were conducted with guiding questions and the analysis of the data was done through the content analysis’ method using Laurence Bardin’s theoretical reference. RESULTS: The discourses resulted in two thematic units, of wich the first was "perspectives of learning in veterinary surgery", divided into the categories of satisfactory theoretical learning, unsatisfactory practical learning, satisfactory practical learning in the internship, satisfactory theoretical-practical learning and poor theoretical-practical learning, and the second thematic unit "teaching in veterinary surgery" divided into categories teaching-learning process, need to increase practical workload and need for teacher improvement